Healthy eating index analysis: Ambato and Pillaro case of study - Franco Crespo, Christian David; Lozada Guevara, Landy Fernanda; Sandra Baldeón-Báez, Sandra Baldeón-Báez (SATHIRI, 2021)
The objective of this research was to comparatively analyze the diets of a small group of rural and urban families in the cities of Ambato and Pillaro, respectively, by applying healthy eating indicators. The Pillaro population analyzed was 56 farmers and 220 individuals from the Ambato area. The findings show the availability of a wide range of foods, and especially fruits, vegetables, and legumes. On the other hand, in urban areas processed products such as rice, sugar, and bread are consumed 4 or more times per week. Rural residents with knowledge of agroecology amount to 71 percent of the population, and 75 percent of the people in the urban zone claim to consume organic products. Finally, the Healthy Eating Index shows that the urban population may benefit from better eating habits, having reached a score of only 45.5, while the score obtained by farmers is 79.5, which indicates a healthy diet.